Effects of two weeks of daily apnea training on diving response, spleen contraction, and erythropoiesis in novel subjects. Issue 3 (29th September 2011) - Engan, H.; Richardson, M. X.; Lodin‐Sundström, A.; van, M.; Schagatay, E.
<x xml:space="preserve">Abstract</x> Three potentially protective responses to hypoxia have been reported to be enhanced in divers: (1) the diving response, (2) the blood‐boosting spleen contraction, and (3) a long‐term enhancement of hemoglobin concentration (Hb). Longitudinal studies, however, have been lacking except concerning the diving response. Ten untrained subjects followed a 2‐week training program with 10 maximal effort apneas per day, with pre‐ and posttraining measurements during three maximal duration apneas, and an additional post‐training series when the apneic duration was kept identical to that before training. Cardiorespiratory parameters and venous blood samples were collected across tests, and spleen diameters were measured via ultrasound imaging. Maximal apneic duration increased by 44 s (P < 0.05). Diving bradycardia developed 3 s earlier and was more pronounced after training (P < 0.05). Spleen contraction during apneas was similar during all tests. The arterial hemoglobin desaturation (SaO2) nadir after apnea was 84% pretraining and 89% after the duration‐mimicked apneas post‐training (P < 0.05), while it was 72% (P < 0.05) after maximal apneas post‐training. Baseline Hb remained unchanged after training, but reticulocyte count increased by 15% (P < 0.05). We concluded that the attenuated SaO2 decrease during mimic apneas was due mainly to the earlier and more pronounced diving bradycardia, as no enhancement of spleen contraction or Hb had occurred. Increased reticulocyte count suggests augmented erythropoiesis.